2013
DOI: 10.3390/ijms140816554
|View full text |Cite
|
Sign up to set email alerts
|

Skp2 Regulates Subcellular Localization of PPARγ by MEK Signaling Pathways in Human Breast Cancer

Abstract: Nuclear hormone receptor family member PPARγ plays an important role in mammary gland tumorigenesis. Previous studies have shown PPARγ has cytoplasmic activities upon tetradecanoyl phorbol acetate (TPA) stimulation. However, the clinical pathological significance of cytoplasmic PPARγ is not completely understood in human breast cancer. Skp2 is oncogenic, and its frequent amplification and overexpression correlated with the grade of malignancy. In this study, the role of cytoplasmic PPARγ and Skp2 expression wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…leprae recognition with excess of free mannose inhibited PPARγ activation. PPARγ is a master transcriptional factor regulating multiple cellular functions, including lipid metabolism and foam-cell generation [ 54 – 57 ]. The role of PPARγ and subsequent lipid-droplet biogenesis in mycobacterium-infected macrophages has also been described [ 37 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…leprae recognition with excess of free mannose inhibited PPARγ activation. PPARγ is a master transcriptional factor regulating multiple cellular functions, including lipid metabolism and foam-cell generation [ 54 – 57 ]. The role of PPARγ and subsequent lipid-droplet biogenesis in mycobacterium-infected macrophages has also been described [ 37 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was demonstrated that casein-kinase-II-dependent phosphorylation of PPARγ leads to subcellular translocation of PPARγ from cytoplasm to nucleus regulated by CRM1 and that urokinasetype plasminogen activator promoted atherogenesis in hepatocytes by downregulating PON1 gene expression via PPARγ nuclear export mechanism [9,40]. Intracellular distribution of PPARγ was observed in BC tissues and cell lines [41], suggesting that poorly differentiated samples and highly invasive cell lines displayed mainly cytoplasmic PPARγ expression. Moreover, cytoplasmic localization of PPARγ was described as being mediated by Skp2 upon MEK1-dependent mechanism indicating cytoplasmic translocation of PPARγ promoted tumorigenesis in BC.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, MEK1 was recently described to have important roles in T cell transcriptional responses through regulation of the nuclear receptor corepressor silencing mediator of retinoid and thyroid hormone (SMRT) at the promoter of c-Fos (39). In addition, there have been reports describing the interactions between PPAR-γ and the activation of MEK1/2-ERK1/2 (40), and MEK1 itself can play a role in regulating nuclear localization and activation of PPAR-γ (41)(42)(43). PPARs have important roles in regulating macrophage responses to inflammation (44,45), and represents one of likely many potential mechanisms by which MEK1/2-ERK1/2 regulates macrophage responses.…”
Section: ) Erk1mentioning
confidence: 99%